Associations between Mn-SOD genetic polymorphism and schizophrenia - Akyol, Omer; Elyas, Halit; Canatan, Halit; Akin, Haluk; Yuce, Huseyin; Yanik, Medaim; Ozyurt, Huseyin (Pergamon-Elsevier Science Ltd, 2006)
[Abstract Not Available]